2019
DOI: 10.5194/hess-2019-120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater / meltwater interaction in proglacial aquifers

Abstract: Abstract. Groundwater plays a significant role in glacial hydrology and can buffer changes to the timing and magnitude of meltwater flows. However, proglacial aquifer characteristics or groundwater dynamics in glacial catchments are rarely studied directly. We provide direct evidence of proglacial groundwater storage, and quantify multi-year groundwater-meltwater dynamics, through intensive and high resolution monitoring of the proglacial system of a rapidly retreating glacier, Virkisjökull, in SE Iceland. Pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…This is made up of loosely consolidated, moderately to poorly sorted, dominantly medium-to F I G U R E 1 Study site including topographical map of Virkisá river basin and proglacial sandur groundwater catchment with instrumentation (a); conceptual model of water flow along cross section from glacier to groundwater adapted from Ó Dochartaigh et al (2019) (b); and photograph of sandur floodplain, meltwater channels and Virkisjökull taken from the southern boundary of the groundwater catchment (c) coarse-grained glaciofluvial sand, gravel and cobbles which have been deposited from actively shifting meltwater streams and frequent (c. 5 per century) jökulhlaups (Robinson, Fairchild, & Russell, 2008). Geophysical evidence from Tromino® passive seismic surveys indicate the deposits are up to 150 m thick within several kilometres of the lake outlet (Ó Dochartaigh et al, 2019). The Virkisá groundwater catchment forms part of the world's largest sandur, Skeiðarársandur.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…This is made up of loosely consolidated, moderately to poorly sorted, dominantly medium-to F I G U R E 1 Study site including topographical map of Virkisá river basin and proglacial sandur groundwater catchment with instrumentation (a); conceptual model of water flow along cross section from glacier to groundwater adapted from Ó Dochartaigh et al (2019) (b); and photograph of sandur floodplain, meltwater channels and Virkisjökull taken from the southern boundary of the groundwater catchment (c) coarse-grained glaciofluvial sand, gravel and cobbles which have been deposited from actively shifting meltwater streams and frequent (c. 5 per century) jökulhlaups (Robinson, Fairchild, & Russell, 2008). Geophysical evidence from Tromino® passive seismic surveys indicate the deposits are up to 150 m thick within several kilometres of the lake outlet (Ó Dochartaigh et al, 2019). The Virkisá groundwater catchment forms part of the world's largest sandur, Skeiðarársandur.…”
Section: Study Sitementioning
confidence: 99%
“…Shallow borehole investigations have shown that the groundwater flows downstream, approximately parallel to the river (Ó Dochartaigh, MacDonald, Wilson, & Bonsor, 2012). However, stable isotope data have shown that there is a zone of meltwater-groundwater mixing within 500 m of river channel where more than 25% of groundwater is derived from mountain meltwater runoff (Ó Dochartaigh et al, 2019). River-aquifer water exchanges in both directions are promoted by the shallow water table which is typically between 0 and 4.4 m below ground level.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…In the 19th and early 20th Centuries, groundwater, abstracted largely from Carboniferous bedrock aquifers in and around Glasgow, was widely used in industries that included distilling, brewing and other food and drink manufacture, dye works, iron works, sawmills, chemical manufacture, printing, shipbuilding and laundries (Ó Dochartaigh et al . 2011). Extensive groundwater abstraction also occurred from coal-bearing Carboniferous rocks during mine dewatering operations, with an estimated total abstraction at peak dewatering activity of approximately 215,000m 3 day –1 (Ó Dochartaigh et al .…”
mentioning
confidence: 99%
“…Extensive groundwater abstraction also occurred from coal-bearing Carboniferous rocks during mine dewatering operations, with an estimated total abstraction at peak dewatering activity of approximately 215,000m 3 day –1 (Ó Dochartaigh et al . 2007). As industrial activity declined during the 20th Century, so did groundwater abstraction, and by the early 21st Century there were only a handful of groundwater abstraction boreholes within the city boundary, all from bedrock.…”
mentioning
confidence: 99%